2017
DOI: 10.1021/acs.organomet.7b00106
|View full text |Cite
|
Sign up to set email alerts
|

Well-Designed Unsymmetrical Salphen-Al Complexes: Synthesis, Characterization, and Ring-Opening Polymerization Catalysis

Abstract: The unsymmetrical salphen ligand (3,5- t Bu-1-OH-C6H2)­CHN-C6H4-NCH­(3-Ph-1-OH-C6H3) ( t Bu‑Ph L­H 2 ) was designed and synthesized to support aluminum complexes. Its symmetric analogues, (3,5- t Bu-1-OH-C6H2)­CHN-C6H4-NCH­(3,5- t Bu-1-OH-C6H2) ( t Bu LH 2 ) and (3-Ph-1-OH-C6H3)­CHN-C6H4-NCH­(3-Ph-1-OH-C6H3) ( Ph LH 2 ), were also explored and compared. The methane elimination reactions between ligands and AlMe3 resulted in formation of t Bu‑Ph L­Al­Me (1), t Bu L­Al­Me (2), and Ph L­… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…The increase in bulkiness also possibly retards rate of binding of the incoming monomer to the metal site. Even though literature suggests that symmetry affects the catalytic activity, the activities of the unsymmetrical complexes reported in this work are comparable to our previous work using symmetrical formamidine ligands . For instance, a similar paddlewheel Cu(II) complex with symmetrical ligands ( k app = 0.0441 h ‐1 ) is comparable to the unsymmetrical complex 3 ( k app = 0.0543 h ‐1 ).…”
Section: Resultssupporting
confidence: 81%
“…The increase in bulkiness also possibly retards rate of binding of the incoming monomer to the metal site. Even though literature suggests that symmetry affects the catalytic activity, the activities of the unsymmetrical complexes reported in this work are comparable to our previous work using symmetrical formamidine ligands . For instance, a similar paddlewheel Cu(II) complex with symmetrical ligands ( k app = 0.0441 h ‐1 ) is comparable to the unsymmetrical complex 3 ( k app = 0.0543 h ‐1 ).…”
Section: Resultssupporting
confidence: 81%
“…However, there are few able to prepare stereoregular PLA from a feedstock of rac -LA. (Stanford and Dove, 2010 ; Thomas, 2010 ; Dijkstra et al, 2011 ) Salen-Al metal complexes and the derivatives reported by Spassky et al ( 1996 ) and others (Radano et al, 2000 ; Nomura et al, 2002 , 2007 ; Ovitt and Coates, 2002 ; Zhong et al, 2002 , 2003 ; Majerska and Duda, 2004 ; Hormnirun et al, 2006 ; Du et al, 2007 ; Luo et al, 2017 ) have attracted the most attention in the last two decades. Correspondingly, two distinguishing mechanisms, enantiomorphic site control mechanism (Ovitt and Coates, 2002 ) and chain end control mechanism (Nomura et al, 2002 ), have been proposed for the production of isotactic polymer (PLLA or PDLA) and stereoblock PLA, respectively.…”
Section: Introductionmentioning
confidence: 91%
“…In the past decades, many new catalysts or initiators, such as enzymatic (Duskunkorur et al, 2015 ), metal-based (O'Keefe et al, 2001 ; Jensen et al, 2004 ; Arbaoui et al, 2008 ; Arbaoui and Redshaw, 2010 ; Carpentier, 2010 ; Sauer et al, 2013 ; Mou et al, 2014 ; Walton et al, 2014 ; Liu et al, 2017 ; Luo et al, 2017 ; Wang et al, 2017 ; Xu et al, 2017 ; Shi et al, 2018a , b ) and organic catalysts (Kamber et al, 2007 ; Song et al, 2017 ), have been reported for conventional ROP of LA (Dechy-Cabaret et al, 2004 ). However, there are few able to prepare stereoregular PLA from a feedstock of rac -LA.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl-and benzyloxy Al complexes bearing salphen ligands ( Figure 44) were also found active in the ROP of rac-lactide (Table 11) [128]. In the case of compound 300, the active species was generated in situ upon addition of an equimolar amount of BnOH; however, the Mn of the isolated polymer was higher than the calculated value, indicating only a partial activation.…”
Section: Aluminummentioning
confidence: 98%